Bioplastics from sweet potatoes - Muhamad, Aida; Mohamad Zamri, Muhamad Adham Zuhri; Rosli, Abdul Hakimi; Abu Hassan Shaari, Nur Aqilah (Penerbit UTHM, 2020)
As oil runs out and the use of fossil fuels becomes expensive, the need for replacement source of raw material for the manufacture of plastics becomes essential. Bioplastics are essential as an alternative of commercial plastics from fossil fuels. Bioplastics are eco-friendly and biodegradable hence provide an effective way to replace the commercial plastics. Producing bioplastics from three types of sweet potatoes which are white, orange and purple in colour is the main goal of the study. Extraction techniques were applied to obtain starch from the sweet potatoes. The starch was then mixed with chemical solution such as glycerine, vinegar and distilled water to form bioplastic. The bioplastics were tested for biodegradability, stretch and water adsorption tests. The results show that the bioplastics from white potatoes degrade faster than the other types of sweet potatoes while commercial plastics cannot be degraded at all. White sweet potatoes have less absorption of water which it is the best criteria for bioplastics. Stretchable of white sweet potatoes is more compared to the other types of sweet potatoes. Bioplastics from white sweet potatoes have a good potential as a replacement of commercial plastics.